Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To transform the given equation [tex]\(y = 3x + 7\)[/tex] into standard form, which has the structure [tex]\(Ax + By = C\)[/tex], follow these steps:
1. Start with the given equation:
[tex]\[ y = 3x + 7 \][/tex]
2. Rearrange the equation to move all the terms to one side. We want to have [tex]\(x\)[/tex] and [tex]\(y\)[/tex] on the left side of the equation and the constant term on the right side.
Subtract [tex]\(3x\)[/tex] from both sides to isolate the terms involving [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ -3x + y = 7 \][/tex]
3. Multiply through by [tex]\(-1\)[/tex] (if necessary) to ensure that the coefficient of [tex]\(x\)[/tex] is positive, according to the standard form convention. In this case, the coefficient of [tex]\(x\)[/tex] is already positive when we rearrange, so this step isn't needed.
Therefore, the equation remains:
[tex]\[ 3x - y = -7 \][/tex]
In standard form [tex]\(Ax + By = C\)[/tex], the coefficients are:
[tex]\[ A = 3, \quad B = -1, \quad C = -7 \][/tex]
So, the equation [tex]\(y = 3x + 7\)[/tex] can be written in standard form as:
[tex]\[ 3x - y = -7 \][/tex]
1. Start with the given equation:
[tex]\[ y = 3x + 7 \][/tex]
2. Rearrange the equation to move all the terms to one side. We want to have [tex]\(x\)[/tex] and [tex]\(y\)[/tex] on the left side of the equation and the constant term on the right side.
Subtract [tex]\(3x\)[/tex] from both sides to isolate the terms involving [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ -3x + y = 7 \][/tex]
3. Multiply through by [tex]\(-1\)[/tex] (if necessary) to ensure that the coefficient of [tex]\(x\)[/tex] is positive, according to the standard form convention. In this case, the coefficient of [tex]\(x\)[/tex] is already positive when we rearrange, so this step isn't needed.
Therefore, the equation remains:
[tex]\[ 3x - y = -7 \][/tex]
In standard form [tex]\(Ax + By = C\)[/tex], the coefficients are:
[tex]\[ A = 3, \quad B = -1, \quad C = -7 \][/tex]
So, the equation [tex]\(y = 3x + 7\)[/tex] can be written in standard form as:
[tex]\[ 3x - y = -7 \][/tex]
Answer:
3x - y = - 7
Step-by-step explanation:
The equation of a line in standard form is
• Ax + By = C ( A is a positive integer and B, C are integers )
given the equation
y = 3x + 7 ( subtract 3x from both sides )
- 3x + y = 7 ( multiply through by - 1 )
3x - y = - 7 ← in standard form
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.